2019
DOI: 10.29333/iji.2019.12447a
|View full text |Cite
|
Sign up to set email alerts
|

Writing Anxiety among Indonesian EFL Students: Factors and Strategies

Abstract: Writing anxiety is a term for a wide variety of apprehensive and pessimistic feelings about writing. The purpose of this study is to identify factors contributing to writing anxiety experienced by EFL students in writing essays and the strategies they apply to manage it. The possible factors of the anxiety were elaborated into close-ended questionnaire items that were distributed to the sampled students followed by open-ended questionnaire item on strategies to deal with the anxiety. The findings indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 13 publications
(54 reference statements)
2
40
0
Order By: Relevance
“…In their research Negari and Rezaabadi (2012) found that students with higher level of anxiety performed better in all aspects of their writing assignment. Such finding strengthens the dichotomy of the role of anxiety in student's writing performance (Jawas, 2019).…”
Section: B Studies About Writing Anxietysupporting
confidence: 79%
“…In their research Negari and Rezaabadi (2012) found that students with higher level of anxiety performed better in all aspects of their writing assignment. Such finding strengthens the dichotomy of the role of anxiety in student's writing performance (Jawas, 2019).…”
Section: B Studies About Writing Anxietysupporting
confidence: 79%
“…Some scholars agree that linguistic difficulties (spelling, grammar, and vocabulary), test anxiety (especially fear of unfamiliar content), lack of topical knowledge, low self-confidence in writing, and fear of teachers' negative comments, and lack of writing practice (Cheng, 2002;Zhang, 2011;Jennifer& Ponniah, 2017) are the major causes of anxiety. Furthermore, Jawas (2019) found that students become more anxious when they are given an in-class assignment. In addition, Kelly & Gaytan (2019) added that instructors' immediate behaviors and instructional clarity are two factors causing anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Jawas [6] found Indonesian students also have English language anxiety because they lack proficiency in writing, and the instructors present them with class essay assignments that probably increase their anxiety because of the limited time in class to finish the assignment with the appropriate answer. Also, some Indonesian students have anxiety when giving a presentation.…”
Section: The Factors That Cause Students' Anxiety At Higher Educationmentioning
confidence: 99%
“…Also, video games online can improve communication among students, increase students' confidence, and reduce their anxiety [34]. Collaborative work among students can also reduce students' anxiety, and they should be encouraged to use the strategies they prefer in learning [6].…”
Section: Improving Relationships Between Faculty Members and Studentsmentioning
confidence: 99%